TECHNOLOGICAL PEDAGOGICAL CONTENT KNOWLEDGE (TPACK) IN THE INSTRUCTION DESIGN OF THE PARTICIPANTS IN TEACHER PROFESSION EDUCATION: A NARRATIVE INQUIRY CASE STUDY - Endang Mastuti Rahayu; Endah Yulia Rahayu; Nico Irawan (Kwangsan: Jurnal Teknologi Pendidikan, 2023)
This study aims to assess pre-service and in-service teacher competency mastery in the Teacher Professional Education Program (PPG). Ultimately, teachers must integrate their pedagogy and content knowledge with technology or Pedagogical Technology content knowledge (TPACK) as a learning technique that highlights certain technologies and applications. Narrative inquiry case studies were used in this study to examine how 12 PPG members applied TPACK personally and publically, as well as their implementation experiences and disputes. In addition, this study confirms prior findings that technology integration improves the work efficiency of in-service EFL instructors. Finally, this study found that pre-service FLE teachers defined their experiences and stories using TPACK-related adjectives such as instructional, consistent with aims, appropriate to PPG targets, thought-provoking, and innovative.AbstrakPenelitian ini bertujuan untuk menilai penguasaan kompetensi guru prajabatan dan dalamjabatan pada Program Pendidikan Profesi Guru (PPG). Pada akhirnya, guru harus mengintegrasikan pengetahuan pedagogi dan kontennya dengan teknologi atau Pedagogical Technology content knowledge (TPACK) sebagai teknik pembelajaran yang menonjolkan teknologi dan aplikasi tertentu. Studi kasus penyelidikan naratif digunakan dalam penelitian ini untuk mengkaji bagaimana 12 anggota PPG menerapkan TPACK secara pribadi dan publik, serta pengalaman dan perselisihan implementasi mereka. Selain itu, penelitian ini menegaskan temuan sebelumnya bahwa integrasi teknologi meningkatkan efisiensi kerja instruktur EFL dalam pelayanan. Akhirnya, penelitian ini menemukan bahwa guru FLE pra-jabatan mendefinisikan pengalaman dan cerita mereka menggunakan kata sifat terkait TPACK seperti instruksional, konsisten dengan tujuan, sesuai dengan target PPG, merangsang pemikiran, dan inovatif.